SYSTEMATIC REVIEW: EVALUATION OF DIAGNOSTIC ACCURACY AND PRACTICAL USEFULNESS OF RAPID DIAGNOSTIC TESTS FOR MALARIA - Hayati, Taureni; Rahman, Fawwaz Fathur; Harlinda, Rhevita Apsari; Yukahadi, Abdi Lathif; Maghfiroh, Dina; Ichwan, Faqusierra Puti; Azzahra, Ghitanisa; Amabel, I Made Glorya; H, Mochammad Risyad Ghifari; Pahlevi, Muhammad Dzaki; Urrahmah, Nafisa; Rini, Oktavia Dwi Sapto (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Malaria remains a significant global health concern, with 249 million cases and 608,000 deaths reported in 2022. Early detection, especially in endemic and resource-limited settings, is crucial to interrupt transmission. Rapid Diagnostic Tests (RDTs) are widely used due to their speed and practicality, requiring no laboratory infrastructure. This review aimed to evaluate the diagnostic accuracy (sensitivity and specificity) of conventional RDTs (HRP2, pLDH, combination) and ultra-sensitive RDTs (uRDTs), and compare their effectiveness across different populations and clinical settings. Literature searches were conducted in PubMed, ScienceDirect, and Cochrane (2020–2025), including studies in English or Indonesian. A total of 30 studies were included based on the PRISMA guidelines, with study populations encompassing children, neonates, adults, pregnant women, clinical patients, and community members in both endemic and imported settings (involving more than 50,000 individuals in total). Most RDTs demonstrated high specificity (>90%), but sensitivity varied widely (0 to >95%), influenced by parasitemia level and population characteristics. HRP2-based RDTs were effective for Plasmodium falciparum, but HRP2 gene deletions caused false negatives. pLDH-based RDTs performed better in multi-species infections. U-RDTs improved the detection of low-density parasitemia, especially in pregnant women and asymptomatic individuals. However, sensitivity declined in neonates and adults with low parasitemia. While some RDTs outperformed microscopy in clinical sensitivity, PCR remains the gold standard, especially for detecting subclinical infections. In conclusion, RDTs provide rapid and specific detection, particularly for moderate to high-density P. falciparum infections. However, in low-density or asymptomatic cases, their limited sensitivity necessitates confirmatory testing using microscopy or PCR.